Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.